From Image to Action: How Brand Image and Product Quality Shape Purchase Decisions through Brand Trust - Afifah Nur Faizah; Rini Hidayati; Amin Mansur (SAN Scientific, 2025)
This study examines the effect of brand image and product quality on purchasing decisions, with brand trust as an intervening variable. The population consists of consumers who have purchased and used Buttonscarves hijabs in Central Jakarta, with a sample of 115 respondents selected through purposive sampling. Using a quantitative method, data were collected via questionnaires and analyzed with SPSS and PLS-SEM. The results show that brand image and product quality both have positive and significant effects on purchasing decisions. Brand image and product quality also positively and significantly influence brand trust. Furthermore, brand trust has a positive and significant effect on purchasing decisions. However, brand trust does not mediate the relationship between brand image and purchasing decisions but does mediate the effect of product quality on purchasing decisions. The managerial implication suggests that management should collaborate with marketing professionals to strengthen brand image, build consumer trust, and maintain consistent communication regarding product quality standards across all organizational levels.